(untitled) (VETERINARIA, 2024)
Auscultation and percussion are complementary and essential tools in the veterinary physical examination of the respiratory system, but they are ineffective in assessing the nature and extent of pulmonary pathology. In this clinical study, we have followed up on four cases of severe bovine respiratory disease. A general clinical examination was carried out, beginning with inspection, measurement of body temperature, and examination of the mucous membranes. Auscultation and percussion were the two key methods of physical examination. After that, the entire pulmonary field on both sides of the thorax underwent a sonographic examination. Results have shown that LUS combined with physical examination enabled a fairly accurate diagnosis and prognosis to be made in adult cows suffering from pulmonary disorders. The discussion of the results also provided an overview of some of the concepts involved in LUS and how they may relate to the findings of an ordinary clinical examination.